The Cipriano Cid Memorial Library at the U.P. Institute of Industrial Relations user needs and information-seeking behavior - Magday, Edralin O. (1986)
Delivery of effective information services is not possible without the identification and assessment of the users' information needs and their information-seeking behavior patterns. This study was designed to identify the information needs and information-seeking behavior of the users of the CCM Library of the Institute of Industrial Relations, University of the Philippines. The main purpose of this study was to make recommendations for the CCM Library to enable it to render better service to its users. The specific objectives are: 1) To identify information-seeking behavior pattern of different types of users of the CCM Library; 2) To ascertain the users' awareness of the information services provided and which of these they prefer; 3) To know how users perceive the services rendered by the CCM Library staff; and 4) To highlight some problem areas and recommendations to improve the information services of the CCM Library.